BENDAMUSTINE AND RITUXIMAB AS FIRST LINE TREATMENT IN SPLENIC MARGINAL ZONE LYMPHOMAS of ELDERLY PATIENTS. - Roberto Castelli (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Splenic marginal zone lymphoma (SMZL) is a chronic B-cell lymphoproliferative disorder, comprising less than 2% of non-Hodgkin’s lymphomas, and affecting mainly middle-aged and elderly patients with a median survival of >10 years. The typical clinical features of SMZL include splenomegaly. Treatment should be patient-tailored and can range from a ‘watchful waiting’ approach for asymptomatic patients without cytopenias to surgery, localized radiation therapy or immuno/chemotherapies. Recently, the combination of Rituximab and Bendamustine (R-Benda) has been defined as highly active in patients with follicular lymphomas, but little is known about the efficacy of R-Benda in SMZL.